DESEMPENHO DE PACUS (PIARACTUS MESOPOTAMICUS) ALIMENTADOS COM FARINHA DE BOCAIUVA (ACROCOMIA ACULEATA) - SANTOS, Vitória Trindade; SILVEIRA, Ulisses Simon; LIMA, Alércio Souza; DIONIZIO, Bruna Gasparini; GONÇALVES, Giovana de Arruda Castelo; PASQUETTI, Tiago Junior (ANAIS DO ENIC, 2018)
-